STRATEGI BRANDING DESTINASI WISATA KAWASAN WISATA INTERNASIONAL BINTAN RESORTS PASCA PANDEMI COVID 19 (The Commercium, 2023)
This study aims to find out how the branding strategy for tourist destinations in the international tourist area of ​​Bintan Resorts after the COVID 19 pandemic was carried out by PT Bintan Resort Cakrawala as the master developer of the Bintan Resorts tourist area by looking at how positioning, differentiation and branding were carried out by PT Bintan Resort Cakrawala. This research is a qualitative research using the case study method. The paradigm used in this study is the constructivism paradigm. Data collection was obtained from interviews, observation and documentation. The results of this study indicate that the positioning strategy developed by PT Bintan Resort Cakrawala is to instill in the minds of tourists that the Bintan Resorts area is a safe area has also made Bintan Resorts the only tourist destination in Indonesia that has received two certifications from the Government of Indonesia and the Government of Singapore. The results showed that the master developer of the international tourist area of ​​Bintan Resorts, PT Bintan Resort Cakrawala has succeeded in carrying out a post-COVID-19 pandemic branding strategy through positioning, differentiation and branding strategies measured based on an increase in the number of tourists and has become a tourist destination trusted by tourists after the COVID-19 pandemic.